سياسة حماية المستهلك في ظل شفافية الممارسات التجارية - يعقوب, محمد كامل (جامعة الوادي university el-oued)
"من المسائل التي تؤرق النشاط الاقتصادي بصفة عامة موضوع حماية المستهلك الذي يشكل عبئا كبيرا على الأعوان الاقتصاديين ،ولاسيما في ظل حرية المنافسة التجارية التي أقرها المشرع الجزائري في دستوره وسنها بنصوص قانونية صارمة تحد من هيمنة الطرف القوي في العلاقة التعاقدية على الطرف الضعيف كونه في أغلب الأحيان لا يعلم يقينا ،طوعا أوكرها كيفية التعامل عندما يريد اقتناء سلعا أو الحصول على الخدمات. وبناء على ما تقدم فالقانون 04-02 من أهم هذه النصوص التي تبنت هذا التصور القائم على الحماية بالدرجة الأولى من خلال سلسلة من الالتزامات المفروضة على العون الاقتصادي من بواسطة شفافية الممارسات التجارية المذكورة في الباب الثاني من القانون السالف الذكر في مظهرين لا ثالث لهما هما الالتزام بالإعلام بالأسعار والتعريفات وشروط البيع في التعاقد وكذا الالتزام بالفاتورة أثناء التعاقد. وهذا مما أدى بالمشرع إحاطة حماية المستهلك بجملة من العقوبات لعلها تردع ا لعون الاقتصادي الذي يخل بالتزاماته التجارية عمدا وسهوا ""One of the issues disturbs economic delivit in general is the issue of consumer protection ,which has become a heavy burden on economic agents, especially in light of the freedom of commercial competition approved by the Algerian legislation in the constition and enacted by strict legal texts ,in its introduction to law04/02. The goal is to reduce the dominance of the strong party in the contractual relationship over the weak party, because he does not know with certainly volun he tarily,I deny how to deal when he wants to acquire goals or obtain services. Based on for going, law no/04/02 related to the transparency and integrity is one of the most important of the relegislative texts that devoted a policy of consumer protection in the first place through a series of obligation imposed on economic and through transparency of commercial practices mentioned in chapter two of the aforementioned law, two manifestations of the third: -Compliance with the notification of prices, tariffs and conditions of sale before contracting. -compliance with the in voice often contracting This is what led the Algerian legislation to surround consumer protection with a set of preventive and deterrent penalties that must be imposed on economic and that deliberately violates its commercial obligations or neglects it "
م.س.ع.21
Keywords: ممارشات تجارية، الشفافية، سياسات عامة ، المديرية الولائية للتجارة ، المعاملة التجارية في الاسلامية; Recherche en recherche commerciale, politiques générales, direction générale du commerce, transaction commerciale en islam